Etos Kerja Guru Madrasah di Ciemas Kabupaten Sukabumi - Dimyati, Didim; Giu, Isra Yanuar; Firdaus, Fadli (Perkumpulan Peneliti dan Pegiat Literasi, 2022)
The purpose of this research. 1) How much influence does organizational culture have on the work ethic of madrasa teachers partially? 2) How much influence do professional aspirations have on the work ethic of madrasa teachers partially? 3) How big is the influence of teacher motivation on the work ethic of madrasa teachers partially? 4) How much influence do organizational culture and professional aspirations have on the work ethic of madrasah teachers partially? 5) How much influence do organizational culture and teacher motivation have on the work ethic of madrasah teachers partially? 6) How big is the influence of professional aspirations and teacher motivation on the work ethic of madrasa teachers partially? 7) How much influence does organizational culture, professional aspirations and teacher motivation have on the work ethic of madrasa teachers simultaneously? This study uses quantitative methods. The results showed that the work ethic of madrasa teachers contributed to a significant increase in results. This means that the higher the work ethic, the higher the work ethic of madrasa teachers.